The Effect of Supervision, Commitment, and Work Discipline on Employee Performance: JEL Classification: M10, M12, M54, J24, H83 - Ami Novrindah Primiatmi A Latief; Muliyadi Hamid; Mujahid Mujahid (Journal La Bisecoman, 2026)
This study aims to analyze the effect of supervision, work commitment, and work discipline on employee performance at the Office of the Social Affairs Agency of South Sulawesi Province. The study is motivated by the need to improve civil servant performance in order to achieve effective, accountable, and results-oriented public services, particularly in the implementation of social welfare programs. This research employs a quantitative approach using a survey method. The population consists of all employees of the Social Affairs Agency of South Sulawesi Province, with samples selected through proportional sampling. Data was collected using questionnaires that have been tested for validity and reliability. Data analysis was conducted using multiple linear regression after fulfilling classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. The regression analysis results indicate that supervision, commitment, and work discipline have a positive relationship with employee performance. Supervision has the lowest regression coefficient (β = 0.082), commitment has the highest regression coefficient (β = 0.390) followed by work discipline (β = 0.386). The simultaneous test (F-test) yields an F value of 29.724 with a significance level of 0.000, indicating that the three variables jointly have a significant effect on employee performance. Partially, commitment and work discipline have a significant effect on performance, whereas supervision does not have a significant effect. The adjusted R-square value of 0.541 indicates that 54.1% of the variance in employee performance can be explained by the research model, while the remaining 45.9% is influenced by other factors outside the model.